Control of the band-gap states of metal oxides by the application of epitaxial strain: The case of indium oxide - Walsh, A; Catlow, C; Zhang, K; Egdell, R (2011)
We demonstrate that metal oxides exhibit the same relationship between lattice strain and electronic band gap as nonpolar semiconductors. Epitaxial growth of ultrathin [111]-oriented single-crystal indium-oxide films on a mismatched Y-stabilized zirconia substrate reveals a net band-gap decrease, which is dissipated as the film thickness is increased and the epitaxial strain is relieved. Calculation of the band-gap deformation of In2O 3, using a hybrid density functional, confirms that, while the uniaxial lattice contraction along [111] results in a band-gap increase due to a raise of the conduction band, the lattice expansion in the (111) plane caused by the substrate mismatch compensates, resulting in a net band-gap decrease. These results have direct implications for tuning the band gaps and transport properties of oxides for application in optoelectronic devices. © 2011 American Physical Society.